"Opisthobranch" (mollusks) inventory of the Faro Lake: a Sicilian biodiversity hot spot. Issue 4 (1st October 2016) - Vitale, D.; Giacobbe, S.; Spinelli, A.; De Matteo, S.; Cervera, J. L.
Abstract: A census of the "opisthobranch" fauna in the Faro Lake and connected canals (NE Sicily) has been realized by photo documentation and specimen samplings, carried out monthly from February 2010 to the present. A total of 47 species have been reported, nine of which are cited in the historic and recent literature (from 1969 to 2016) vs. 38 first records; six were non-indigenous species. A major number of species, 16, was found exclusively in the lake with respect to the four species localized in the canals, whilst 10 were shared species. Based on the frequency of records, 24 "occasional", 20 "settled" and three "invasive" species have been distinguished; these latter included two non-indigenous species, Aplysia dactylomela and Bursatella leachii, plus the Mediterranean Dendrodoris limbata, whose recent introduction in the Faro Lake from other Mediterranean lagoons is here postulated.